Systematics of the southern African genus Ixia (Iridaceae: Crocoideae): 4. Revision of sect. Dichone - Goldblatt, Peter; Manning, J.C. (African Biodiversity & Conservation, 2012)
The southern African genus Ixia L. comprises ± 90 species from the winter-rainfall zone of the subcontinent. Ixia sect. Dichone (Salisb. ex Baker) Goldblatt & J.C.Manning, one of four sections in the genus and currently including 10 species and three varieties, is distinguished by the following floral characters: lower part of the perianth tube filiform and tightly clasping the style; filaments not decurrent; upper part of the perianth tube short to vestigial; style branches involute-tubular and stigmatic only at the tips; and so-called subdidymous anthers. We review the taxonomy of the section, providing complete descriptions and distribution maps, and a key to the species. I. amethystina Manning & Goldblatt is recognized to be a later synonym of I. brevituba G.J.Lewis. Most collections currently included under that name represent another species, here described as I. rigida. We recognize five additional species in the section: early summer-blooming I. altissima from the Cedarberg; I. bifolia from the Caledon District; I. flagellaris, a stoloniferous species from the Cedarberg; I. simulans from the western Langeberg; and I. tenuis from the Piketberg. We also raise to species rank I. micrandra var. confusa and var. minor, as I. confusa and I. minor respectively. Foliar and associated floral variation in the widespread I. scillaris has led us to recognize two new subspecies among its northern populations, broad leaved subsp. latifolia and the dwarfed, smaller flowered subsp. toximontana; subsp. scillaris is restricted to the immediate southwestern Cape, from Darling to Somerset West. Sect. Dichone now has 17 species and two subspecies.